Misoprostol (Cytotec) for Prevention of Ovarian Hyperstimulation Syndrome. A Preliminary Investigation. - Formigli Leonardo; Andriamaro Andriantsirombaka Rakotobe; Rija Ramarolahy; Badulli Graziella; Rasoarimanana Hanitra; Ashurova Nargis; Krishnamoorthy Ramachandran (Journal of Fertility Biomarkers, 2019)
This preliminary study explores misoprostol as a preventive strategy for ovarian hyperstimulation syndrome. It outlines rationale, dosing considerations, and early safety signals, and calls for controlled trials to establish efficacy and risk–benefit.
Keywords: Ovarian Hyper Stimulation